2017
DOI: 10.1016/j.solener.2017.07.046
|View full text |Cite
|
Sign up to set email alerts
|

High-flux optical systems for solar thermochemistry

Abstract: a b s t r a c tHigh-flux optical systems (HFOSs) are optical concentrators used to increase the radiative flux of the natural terrestrial solar irradiation. High radiative flux concentration leads to high energy density in solar receivers which allows to obtain high temperatures. In solar thermochemical applications, the hightemperature heat drives endothermic thermochemical reactions. HFOSs have been deployed for research and development of solar thermochemical devices and systems, from solar reacting media t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 104 publications
(121 reference statements)
0
17
0
Order By: Relevance
“…A review conducted by Bushra and Hartmann [10] has shown that most articles published on reflective two-stage solar concentrators deal with applications for power generation using solar cells, and thermo-electric generators. In a work published in 2017, Levêque et al [11] reviewed the designs and characteristics of high-flux optical systems (HFOSs), as well as challenges and opportunities in the area of HFOSs for solar thermochemical applications. This review [11] provides an exhaustive list of point-focusing on-sun HFOSs, showing the characteristics and peak fluxes of existing solar furnaces worldwide (at universities, research institutes, and companies) which use real sunlight, but also of indoor solar simulators.…”
Section: Other Recent Overviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review conducted by Bushra and Hartmann [10] has shown that most articles published on reflective two-stage solar concentrators deal with applications for power generation using solar cells, and thermo-electric generators. In a work published in 2017, Levêque et al [11] reviewed the designs and characteristics of high-flux optical systems (HFOSs), as well as challenges and opportunities in the area of HFOSs for solar thermochemical applications. This review [11] provides an exhaustive list of point-focusing on-sun HFOSs, showing the characteristics and peak fluxes of existing solar furnaces worldwide (at universities, research institutes, and companies) which use real sunlight, but also of indoor solar simulators.…”
Section: Other Recent Overviewsmentioning
confidence: 99%
“…In a work published in 2017, Levêque et al [11] reviewed the designs and characteristics of high-flux optical systems (HFOSs), as well as challenges and opportunities in the area of HFOSs for solar thermochemical applications. This review [11] provides an exhaustive list of point-focusing on-sun HFOSs, showing the characteristics and peak fluxes of existing solar furnaces worldwide (at universities, research institutes, and companies) which use real sunlight, but also of indoor solar simulators. The discrepancy between the spectral power distributions of the solar simulators compared to real solar radiation is normally considered a reasonable compromise, in order to allow for easily controlled and repeatable experiments.…”
Section: Other Recent Overviewsmentioning
confidence: 99%
“…Efforts towards decarbonization of fossil fuels and mitigation of CO2 emissions via solar thermochemical processes have significantly increased over the past few decades. This is not only based on the recent developments of high-flux optical systems [1], but is also supported by the increasing number of new research ideas and inventions [2]. Despite the important progress so far, further development of the current technologies is still required in order to be considered as sustainable replacement for conventional industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…This furnace could reach a power of one megawatt and nowadays continues serving as an installation for studying materials at very high temperatures. In a recent work by Levêque et al [11], the characteristics of "solar furnaces"-in pointfocusing solar concentration facilities located throughout the world, at universities, research institutes, and companies, and operating at concentrations relevant to solar thermochemistry-have been summarized. More recently (2018), state-of-the-art uses of concentrated solar energy applied to materials science and metallurgy have been comprehensively reviewed by Fernández-González et al [12].…”
Section: Introductionmentioning
confidence: 99%